Clean label approach for fresh goat milk: Enhancing microbial safety and shelf-life using High Hydrostatic Pressure (HPP) - Nasharuddin, Raja Arief Deli Raja; Wan Nur Zahidah Wan, Zainon; Nur Baizura, Sa'dom; Arif Zaidi, Jusoh; Hafiz Aizat, Yanan; Ahmad Huzairi Imam, Musaniff; Yangmurni, Zamani; Nur Fadhilah, Sapiee (Department of Agricultural Products Technology, Mulawarman University, 2026)
The clean-label approach has gained global interest as consumers increasingly prefer minimally processed foods without synthetic additives. Concurrently, the demand for goat milk products is rising because of their nutritional and health benefits. This study investigated the application of high hydrostatic pressure (HHP) for controlling microbial growth and inactivating Salmonella typhimurium in fresh Saanen goat milk. Microbiological evaluation of HHP-treated milk samples included an S. typhimurium (ATCC 14028) challenge test and monitoring of total plate count, yeast and mold, coliforms, Escherichia coli, Staphylococcus aureus, lactic acid bacteria, and Salmonella during storage. Specifically, HHP was applied at 600 MPa for 6 min using food-grade spout-pouch packaging, based on prior optimization. HHP milk samples achieved complete inactivation of S. typhimurium, with reductions of 6 log10 CFU/mL at high spike levels and 3 log10 CFU/mL at low spike levels, demonstrating microbial decontamination kinetics. Shelf-life evaluation showed that HHP-treated milk retained acceptable microbiological, physicochemical, and sensory qualities for up to 75 d under chilled storage (2±7 °C), while fresh untreated milk spoiled by day 6, exceeding permissible microbial limits. Beyond 75 d, viscosity degradation was observed in HHP-treated milk. These findings confirm that optimized HHP treatment enhances microbial safety and extends shelf life, supporting its role in developing clean-label goat milk products.